Maintaining military medical skills during peacetime : outlining and assessing a new approach - Eibner, Christine (Rand Corp., 2008)
Military medical personnel are tasked with fulfilling both the benefits mission and the readiness mission of the U.S. Department of Defense (DoD). Currently, most military medical personnel are stationed at military treatment facilities (MTFs) during peacetime, where they maintain their clinical skills by treating beneficiaries of TRICARE, the military health care program. However, the medical skills required during deployment are likely to differ significantly from those required at MTFs. Alternative arrangements for maintaining medical skills for deployment may be needed. One alternative would be to station some military medical personnel in nonmilitary settings where the case mix might more closely resemble the expected case mix under deployment, such as emergency rooms or trauma centers. This study explored one model under which active-duty personnel would be assigned to civilian settings during peacetime, focusing on civilian receptiveness to the proposed arrangement and identifying potential barriers and concerns. Findings indicate that civilian medical organizations are generally receptive to the idea of such a model and that DoD could consider conducting a pilot study to assess the effectiveness of the model in improving military medical readiness.